2018
DOI: 10.1001/jamaophthalmol.2017.6560
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography Assessments of Optic Nerve Sheath Diameter as a Noninvasive and Dynamic Method of Detecting Changes in Intracranial Pressure

Abstract: IMPORTANCE The crtierion standard method for monitoring intracranial pressure (ICP) can result in complications and pain. Hence, noninvasive, repeatable methods would be valuable. OBJECTIVE To examine how ultrasonographic optic nerve sheath diameter (ONSD) correlated with noninvasive and dynamically monitored ICP changes. DESIGN, SETTING, AND PARTICIPANTS The ONSD was measured before the lumbar puncture (LP) in 60 patients on admission. Patients with elevated ICP were divided into group 1 (200 < LP Յ 300 mm H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 30 publications
5
85
0
2
Order By: Relevance
“…20 A previous study published by Launey and colleagues in 2014 22 that included invasive measurements of ICP through an intraventricular catheter and the ONSD before and after using 20% mannitol, found that both measures decreased significantly after using such therapy. Also Wang and co-workers in 2018 23 in his study where they measured the ICP through lumbar puncture and also the ONSD was recorded before and after using etiological and osmotic treatment, with a follow up for 1 month, shows that ICP changes in an invasive an non-invasive way were highly related.…”
Section: Discussionmentioning
confidence: 97%
“…20 A previous study published by Launey and colleagues in 2014 22 that included invasive measurements of ICP through an intraventricular catheter and the ONSD before and after using 20% mannitol, found that both measures decreased significantly after using such therapy. Also Wang and co-workers in 2018 23 in his study where they measured the ICP through lumbar puncture and also the ONSD was recorded before and after using etiological and osmotic treatment, with a follow up for 1 month, shows that ICP changes in an invasive an non-invasive way were highly related.…”
Section: Discussionmentioning
confidence: 97%
“…If the changes in either pEEG monitoring or cerebral saturation are unilateral, and the peripheral or somatic NIRS saturation is normal, localized cerebral hypoperfusion should be suspected. Furthermore, cerebral investigation should be pursued, such as a carotid, jugular, and brain ultrasound, TCD, 15 optic nerve sheath measurement, 16,17 and/or computed tomography. On the other hand, if the cerebral saturation reduction is bilateral and symmetrical and the somatic NIRS saturation is also reduced, then a non-cerebral etiology such as cardiogenic shock, hemorrhagic shock, hypoxemia or obstruction to adequate central venous drainage (superior or inferior vena cava) is more likely, as previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…162 In addition, changes in ICP correlate with reciprocal changes in optic nerve sheath diameter. 198 Similarly, a magnetic resonance imagingeassisted measurement of the width of the orbital SAS has been used to estimate ICP. 204 Finally, venous ophthalmodynamometry has been used to correlate central retinal venous pressure with ICP.…”
Section: Definition and Physiological Implicationsmentioning
confidence: 99%